Evaluation of the Weather Research and Forecasting (WRF) model with respect to wind in complex terrain - Solbakken, Kine; Birkelund, Yngve (Journal of Physics: Conference Series, 2018)
Source at https://doi.org/10.1088/1742-6596/1102/1/012011. In this study the performance of the Weather Research and Forecast (WRF) model in a complex and coastal terrain has been evaluated with focus on wind resource assessment. The study area is a small community on the northern part of the island Senja, Norway. The community, with fishery and seafood as its main industry, is being limited by poor grid connection. One of the solutions is to increase the production of local power from wind energy. There are no in-situ wind measurements in the area, and therefore numerical weather prediction models, namely the WRF model, is being evaluated as a method for wind resource assessment. The WRF model has been run for the whole of 2017 with high resolution covering an area large enough to include the three closest weather stations. The model is compared to the observed wind speed and direction. It is found that the model is able to reproduce the average wind speed and wind direction quite well for two of the locations, while for the third location the average wind speed is considerably overestimated compared to the observations. The Root Mean Square Error (RMSE) and Mean Absolute Error (MAE) found are larger than in other comparable studies.